KATALIS ASAM PADAT SILIKA TERSULFONASI UNTUK PROSES PEMBUATAN MINYAK PELUMAS - Prasetyo, Andrianto; Sembiring, Almira Cristy; Rahmi, Arika Fadhia (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
In the process of crude palm oil (CPO) to be lubricant, homogeneous acid catalyst is commonly used. This kind of catalyst has some disadvantages including the difficulty to remove well from the product and corrosion problem. Therefore, it is necessary to develop solid acid catalyst that is easy to be removed from the product. The purpose of this work were to determine the effect of the template removal method and the concentration of polyethylene glycol (PEG). In this work, solid acid catalyst of sulfonated silica from water glass (sodium silicate) was prepared. The silica pores were expanded by templating using PEG. Two methods were used for template removal: calcination at 550ï°C and solvent extraction using dimethyl sulfoxide (DMSO). The results showed that although calcination provided better performance in removing PEG, the silica produced tended to shrink. On the other hand, solvothermal extraction could avoid the shrinkage to give higher surface area. The higher surface area indicates that there are more active sites available for sulfonate groups to be grafted to exchange silanol groups on the silica surface. The results showed that ionic capacity of the sulfonated-silica obtained by solvothermal extraction was larger than that of calcination. The ionic capacity took the value of approximately 12.603 mmol/g silica. This result approached the ionic capacity of resins that is commonly used as a catalyst in the process of CPO to be lubricant.Â Keywords: Â Crude Palm Oil, Solid Catalyst, Sodium Silicate, Lubricant